2017
DOI: 10.1016/j.kint.2016.10.035
|View full text |Cite
|
Sign up to set email alerts
|

An angiotensin II type 1 receptor binding molecule has a critical role in hypertension in a chronic kidney disease model

Abstract: Angiotensin II type 1 receptor-associated protein (ATRAP) promotes AT1R internalization along with suppression of hyperactivation of tissue AT1R signaling. Here, we provide evidence that renal ATRAP plays a critical role in suppressing hypertension in a mouse remnant kidney model of chronic kidney disease. The effect of 5/6 nephrectomy on endogenous ATRAP expression was examined in the kidney of C57BL/6 and 129/Sv mice. While 129/Sv mice with a remnant kidney showed decreased renal ATRAP expression and develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 40 publications
(58 reference statements)
0
23
0
Order By: Relevance
“…We found an increase of urinary aldosterone excretion after 5/6 Nx, which was similar between strains. Kobayashi et al 29…”
Section: Discussionmentioning
confidence: 99%
“…We found an increase of urinary aldosterone excretion after 5/6 Nx, which was similar between strains. Kobayashi et al 29…”
Section: Discussionmentioning
confidence: 99%
“…Ang II type 1 receptor (AT1R)‐associated protein (ATRAP/Agtrap) is a transmembrane protein localized to the plasma membrane and perinuclear vesicular structures and was originally identified as a low‐molecular‐weight protein that binds to the carboxyl‐terminal domain of AT1R . The strongest expression of ATRAP was found in renal tubules of kidneys, and it also was found in the heart, kidneys, vascular smooth muscle cells, and adipose tissues .…”
Section: Discussionmentioning
confidence: 99%
“…21,22 The strongest expression of ATRAP was found in renal tubules of kidneys, and it also was found in the heart, kidneys, vascular smooth muscle cells, and adipose tissues. [22][23][24] Previous studies showed us that ATRAP could enhance the constitutive internalization of AT1R and suppress the activation of angiotensin II in order to negatively regulate angiotensin II signaling and selectively suppress Ang II-mediated pathological responses. 21 When the body is stimulated by various pathological factors such as highsodium diet and cardiovascular injury, the activation of angiotensin II could be suppressed by ATRAP, which can cause hypertension and organ dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the quantitative analysis of immunofluorescence staining indicated that almost all of the internalized AT1R were associated with ATRAP, indicating that a major function of ATRAP in cultured cells including cardiovascular cells is to promote the constitutive internalization of AT1R [4,13,14]. Furthermore, a transgenic model increase in renal ATRAP expression beyond the baseline in vivo was accompanied by a constitutive reduction of renal plasma membrane AT1R expression and by the promotion of renal AT1R internalization in response to Ang II [15]. In contrast, a genetic deficient model of ATRAP caused an enhanced surface expression of AT1R in the kidney [16].…”
Section: Promoting Effects Of Atrap On At1r Internalizationmentioning
confidence: 99%